Agricultural producer support estimates for developing countries: Measurement issues and evidence from India, Indonesia, China, and Vietnam - Orden, David; Cheng, Fuzhi; Nguyen, Hoa; Grote, Ulrike; Thomas, Marcelle; Mullen, Kathleen; Sun, Dongsheng (International Food Policy Research Institute, 2007)
This study analyzes the evolution of agricultural policies from 1985 to 2002 in India, Indonesia, China, and Vietnam and provides empirical estimates of the degree of protection or disprotection to agriculture in these four countries, both by key commodities and in aggregate... Taken together the reported measures of support and disprotection of specific crops and agriculture in total provide a reasonable basis for assessing the stance of agricultural policies of India, Indonesia, China, and Vietnam. Attention to measurement issues provides a sensitivity analysis. The results reported are indicative of the range of outcomes likely to be found more broadly among developing countries. From regimes of heavy intervention in agricultural markets, each of the four countries in the study has undergone a substantial reform process.